1999
DOI: 10.1007/s004300050115
|View full text |Cite
|
Sign up to set email alerts
|

One-step polymerase chain reaction-based typing of Helicobacter pylori vacA gene: association with gastric histopathology

Abstract: Heterogeneity of the Helicobacter pylori vacA gene may be associated with bacterial virulence and presentation. In this study, the possible correlation between vacA genotypes and gastric histopathology was investigated. Using a modified one-step polymerase chain reaction (PCR)-based method, 122 of 131 H. pylori isolates obtained from 63 of 67 patients from Germany were classified into distinct vacA genotypes according to their signal sequence (s1 or s2) and their midregion alleles (m1 or m2). A possible subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…When both cagA and vacA detection is performed, a strong association exists between the presence of cagA and vacA s1, corresponding to strains with the highest production of cytotoxin (23,202,217,475,547,589) as well as more severe pathology and disease.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…When both cagA and vacA detection is performed, a strong association exists between the presence of cagA and vacA s1, corresponding to strains with the highest production of cytotoxin (23,202,217,475,547,589) as well as more severe pathology and disease.…”
Section: Molecular Methodsmentioning
confidence: 99%
“…The cagA gene status was determined by the presence or absence of cagA amplicons. The vacA genotypes, including signal(s) sequences and midregion (m) types, were characterized by a one-step PCR method (22). For ribotyping, a 1.5-kb fragment was amplified with broad-specificity 16S ribosomal DNA (rDNA) primer pairs pA-f (5Ј-AGAGTT TGATCCTGGCTCAG-3Ј) and pH-b (5Ј-AAGGAGGTGATCCAGCCGCA-3Ј) (15), using an initial denaturation step at 94°C for 2 min, followed by 35 cycles of denaturation at 94°C, annealing at 55°C, and extension at 72°C (each for 1 min), and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…1999 ). One other single‐step vacA genotyping assay has been described previously that used the Atherton primers to amplify the signal region but novel primers to target the mid‐region ( Han et al . 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Han et al . (1999 ) reported that their multiplex assay was unable to determine vacA type in 7% of isolates tested.…”
Section: Discussionmentioning
confidence: 99%